A Brief Study to Clarify Some Aspects Related to Vibrational Density of States for the Far Infrared Range in Amorphous Semiconductors - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
Phonon density of states of amorphous semiconductors for the far-infrared range is examined analytically. On the basis of this formulation, optical absorption corresponding to structural disorder is evaluated and discussed at the far-infrared range for a-Ge and a-Si.